Estudos sobre a interação parasito-hospedeiro: papel das amastinas de Trypanosoma cruzi - Ramon Mendes de Almeida (2011)
Amastins are 170-200 amino acids, highly hydrophobic surface glycoproteins expressed not only in T. cruzi amastigotes but also in amastigotes from several species of Leishmania. The T. cruzi genome contains 12 copies of amastins, which can be subdivided in two groups: the amastins are organized in a cluster containing alternated copies of tuzin genes, differently from amastins which are not. Likewise amastins, mRNA from members of the group is more abundant in amastigotes than in the others stages of the parasite. Analyses of amastin genes present in the genome showed that they encode proteins with increased amino acid variability in the hydrophillic domain that is likely in contact with the host cell cytoplasm. In order to gain new insights of their function, parasites over expressing amastin were generated and yeast two hybrid (Y2H) experiments were performed to identify human proteins able to interact with amastins. Epimastigotes over expressing a amastin gene in fusion with GFP showed higher densities in cultures in comparison to parasites expressing only GFP. From the Y2H experiments, ten positive clones were identified and IL-15 cDNA was present in two of them (Teixeira et al., not published). We observed that IL-15 with a histidine tag interacts with amastin in in vitro pull down experiments. Infection of HEK293T cells expressing intracellular IL-15 with CL Brener trypomastigotes resulted in elevated rates of infection and number of intracellular amastigotes in comparison to non-transfected cells.